Soft Skills and EFL Effective Teaching: (An Investigation of the Link between Educators’ Intangible Abilities and Educational Outcomes) - Prof. Omer Elsheikh Hago Elmahdi; Dr. Asjad Ahmed Saeed Balla (Journal of Arts, Literature, Humanities and Social Sciences, 2024)
This mixed methods study investigates links between EFL teachers’ soft skills and educational outcomes to advance understanding and strengthen teacher preparation and support. A survey will assess 37 EFL teachers’ self-reported skills, practices, and perspectives, while semi-structured interviews with 15 teachers will provide additional context. Quantitative data will reveal self-evaluated competency levels and correlate skills to practices and outcomes. Qualitative data will elucidate teacher experiences and views on soft skills’ connections to effectiveness. Identifying overlooked skills and linking self-assessed limitations to evidence can inform targeted training, standards, and supports to develop EFL teachers’ capacities holistically. Findings will underscore soft skills’ overlooked yet pivotal role in quality EFL teaching. Biases in self-report data and generalizability may exist, however the mixed methods approach can provide a more comprehensive understanding to guide future research. Intentionally developing teachers’ soft skills is critical so they can optimize practices and relationships to benefit diverse learners. This study brings awareness to this key competency domain needing greater focus in policies and professional development.